2005
DOI: 10.17221/4563-jfs
|View full text |Cite
|
Sign up to set email alerts
|

Effects of pressure on the root systems of Norway spruce plants (Picea abies[L.] Karst.)

Abstract: Roots are stressed quire often under natural conditions, e.g. when considering sloping terrain, layers of fluvial deposits, huge layers of melting snow, load of heavy forest machinery during logging and hauling operations, recreational activities of people, high density of deer or cattle, etc. We focused our experiments on Norway spruce (Picea abies [L.] Karst.) seedlings grown in containers with glass walls under the permanent load of 5.1 kPa during the whole growing season. The applied pressure affected root… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
17
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 20 publications
1
17
0
Order By: Relevance
“…Previous studies have shown that the elongation and penetration of primary roots are reduced in a compacted soil, which may induce a lower uptake of nutrients and water (e.g., Kozlowski 1999). This may lead to higher seedling mortality and a reduced tree growth (e.g., Gebauer and Martinková 2005), among other factors dependent on soil type and tree species. Compaction can also induce a shift in the herb layer from interior forest species to more ruderal and pioneer species (e.g., Zenner and Berger 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that the elongation and penetration of primary roots are reduced in a compacted soil, which may induce a lower uptake of nutrients and water (e.g., Kozlowski 1999). This may lead to higher seedling mortality and a reduced tree growth (e.g., Gebauer and Martinková 2005), among other factors dependent on soil type and tree species. Compaction can also induce a shift in the herb layer from interior forest species to more ruderal and pioneer species (e.g., Zenner and Berger 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Higher penetration resistance reduces elongation and penetration of roots, and thus lowers the uptake of water and nutrients (Kozlowski, 1999). A higher seedling mortality and reduced tree growth was observed by Gebauer & Martinková (2005). The level of these effects depends on soil type and examined tree species (Gomez, Powers, Singer & Horwath, 2002;Heninger, Scott, Dobkowski, Miller, Anderson et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…In the last few decades, scientists have begun investigating the effects of soil compaction on root morphological development; nevertheless, few studies have aimed to determine the effect of soil compaction on seedling development by comparing above‐ and below‐ground data (Cambi, Hoshika, et al, ; Gebauer & Martinková, ). According to Bengough and Mullins (), studies on the effect of soil compaction have followed two research lines: empirical measures of soil strength such as penetrometer resistance (Bengough et al, ) or the application of a known resistance to plants growing in an artificial medium compressed by a known pressure (Passioura, ).…”
Section: Introductionmentioning
confidence: 99%
“…In Mediterranean Quercus species, which develop a deep taproot during early growth stages, it was observed that a well-developed root system is a key factor for overcoming summer drought (Cubera, Moreno, & Solla, 2009;Tsakaldimi, Zagas, Tsitsoni, & Ganatsas, 2005). Early, rapid establishment is also important for a forest understory to take advantage of transitory available resources (Jones, Allen, & Sharitz, 1997) In the last few decades, scientists have begun investigating the effects of soil compaction on root morphological development; nevertheless, few studies have aimed to determine the effect of soil compaction on seedling development by comparing aboveand below-ground data (Cambi, Hoshika, et al, 2017;Gebauer & Martinková, 2005). According to Bengough and Mullins (1991), studies on the effect of soil compaction have followed two research lines: empirical measures of soil strength such as penetrometer resistance (Bengough et al, 2011) or the application of a known resistance to plants growing in an artificial medium compressed by a known pressure (Passioura, 2002).…”
mentioning
confidence: 99%
See 1 more Smart Citation